ARGUMENTATIVE ESSAY AND VOCABULARY ENRICHMENT OF ENGLISH STUDENTS BY UTILIZING GOOGLE TRANSLATE (English Community Journal, 2022)
Argumentative essay writing has been becoming a challenge for EFL students as Students must persuade their readers to share their viewpoints on the material they write. Google Translate is regarded as a learning resource that may be used to help pupils with their writing and to broaden their vocabulary.. The objective of this study was to describe how the fourth semester students of English education study program Sriwijaya University utilized Google Translate to improve their writing skills and enhance their vocabulary. This study used the descriptive qualitative method in describing the finding from documentation and a set of the questionnaire given to students to know their opinion about using Google Translate during their learning process. The findings showed that there are both advantages and disadvantages in utilizing Google Translate in writing class for English education students, the advantages were students were able to enrich their vocabulary and improved writing skill as it useful for students to look up words, synonyms, fast result, and students knew how to pronounce a word correctly and the disadvantages were students may find it appeared to produce bad sentence structure if translate long sentence, would not allow them to be creative even could make students become lazy and could lose their confidence and brought them depended on Google Translate.